Mughal Farmān-i-Shāhī and Islamic Jurisprudence - Yasmeen, Dr. Mamoona; Tayyab Khan, Dr. Muhammad (International Research Journal of Arabic and Islamic Studies, 2022)
Though the sources of Farmān-i-Shāhī, according to the Mughal emperors, are those have derived from the Holy Quran, Sunnah and other primary and secondary sources of Sharī‘ah and apparently they are their core sources for the formation of laws as well, but there seemed to be deviation from the set rules of Sharī‘ah conjunctions. It is evident that the Mughal emperors with the help of well-known Islamic Scholars had set a system in a multicultural and multi religious society that reflected the Sharī‘ah in most of the injunctions of Shariah, but still there are many evidences denote that Mughal emperors took up the matters totally against the principles of Sharī‘ah as particular in those challenging their governance and authority. The Study aims to analyze the Farmān-i-Shāhī with special perspective of Islamic Jurisprudence and find out to what extant Farmāns are according to the Sharī‘ah and to what degree they deviated from it.